Tempo livre no trabalho voluntário: o desenvolvimento pessoal sobre as percepções dos coordenadores das pastorais católicas na microrregião de Cascavel - PR - Camargo, William Silvano de (2023)
In this thesis, the relationship between free time and voluntary work in Catholic pastorals in the micro-region of Cascavel - PR and their possible contributions to personal development were analyzed. The theoretical centrality of this work focused on the concept of personal development. The methodological procedures involved a qualitative approach, using theoretical references from Social Sciences, Philosophy, History, Anthropology and Economics, using Critical Discourse Analysis as an analytical form of data, focusing on field research based on of the theoretical method of Communication Systems Thinking. To this end, a script of open questions was applied with the aim of understanding the subjectivities of the responses passed on and transcribed, so that in the end the final analysis could be completed to obtain the results. The general objective was to analyze, through the perceptions of the volunteer coordinators of Pastorals in the microregion of Cascavel - PR, the relationship between volunteer work in free time and the possible promotion of personal development. The specific objectives, in turn, were aimed at demonstrating the effects of voluntary work in free time, identifying characteristics of personal development in voluntary work and how personal development was encouraged in voluntary work. Given these aspects, the research question was this: According to the perceptions of volunteer coordinators, can personal development be stimulated during free time in voluntary work in pastoral care? To answer it, in the second chapter, entitled Free Time: The characteristics of voluntary work for personal development, the connotations of free time were discussed in relation to voluntary work to promote personal development; in the third chapter, called The apparatus of the social organization of Catholic Pastorals, the organization and actions of the Pastorals were demonstrated in their general scope and in the micro-region of Cascavel - PR; in the fourth chapter, Methodological paths of field research, the process of carrying out the methodological research was explained; and in the fifth chapter, entitled Field research tabulations and their respective analyses, the data were tabulated and analyzed using Critical Discourse Analysis. The results revealed that voluntary work in free time provided various syntheses to stimulate personal development, such as vital direction, professional qualification and formal education, need for support from others, exercise of citizenship, institutional approach, family support, notion of belonging and group identification and social recognition, elements that are intertwined in voluntary work and are part of the process of personal development. All these syntheses led to the conclusion that free time in voluntary work stimulates personal development.